2014
DOI: 10.1371/journal.pone.0095094
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Function of Overweight Women with Gestational Diabetes Mellitus – A Cross-Sectional Study

Abstract: Obesity and gestational diabetes mellitus (GDM) are increasing worldwide and may compromise female sexual function. We hypothesize that among GDM patients in the third trimester of pregnancy, those with excess body fat would have worse female sexual function scores than normal weight women. Our aim was to assess the sexual function of overweight compared to normal weight women with GDM. This was a cross-sectional survey involving 143 Brazilian women with GDM in the third trimester of pregnancy: 76 were overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
(69 reference statements)
0
9
1
2
Order By: Relevance
“…As disfunções sexuais ocorrem em ambos os sexos e são definidas pela falta, desconforto e/ou dor no decorrer da resposta sexual, interferindo de forma negativa em alguma fase desse evento (desejo, excitação e/ou orgasmo), podendo causar bloqueios e traumas [7][8][9][10][11][12] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…As disfunções sexuais ocorrem em ambos os sexos e são definidas pela falta, desconforto e/ou dor no decorrer da resposta sexual, interferindo de forma negativa em alguma fase desse evento (desejo, excitação e/ou orgasmo), podendo causar bloqueios e traumas [7][8][9][10][11][12] .…”
Section: Introductionunclassified
“…Isso pode causar desconforto e afetar a sua QV 7,9,13,14 . Durante o período gestacional, essa disfunção pode ocorrer por questões como presença de desconforto físico, receio de machucar o bebê, diminuição da libido e dor durante o ato sexual 8,[15][16][17][18] .…”
Section: Introductionunclassified
“…Besides having a significantly lower mean overall FSFI score, overweight women in the 3rd trimester had significantly lower mean scores in desire, arousal, lubrication, orgasm and dyspareunia domains. In a previous study, Ribeiro et al reported that 67 overweight gestational diabetes patients in the 3rd trimester of pregnancy had significantly lower FSFI scores than 73 normal weight women with gestational diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…Despite some evidence that being overweight may have a negative effect on non‐pregnant women′s sexual function , this topic has not been extensively investigated among pregnant women. In a previous study that analyzed the sexual function of 143 women with gestational diabetes using the Female Sexual Function Index (FSFI) questionnaire, we observed that women with a pre‐pregnancy body mass index (BMI) ≥25 had poorer sexual function than normal weight women .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several Brazilian studies show that female obesity and overweight are related poorer sexual function (Ferraresi, Lara, Reis, & Rosa e Silva, 2013;Martins e Silva, Rego, Galvao, Florencio, & Cavalcante, 2013;Ribeiro et al, 2014;Zueff, Lara, Vieira, Martins Wde, & Ferriani, 2015), which argues against a cultural difference in Brazil. With one single exception, none of these research findings are cited by Lara et al, and the only finding given in support of a direct relation between coital frequency and obesity is a study with Swedish 70-year-olds (Beckman, Waern, Ostling, Sundh, & Skoog, 2014), the findings of which are likely not generalizable to younger ages.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%